Activities Michurin’s circles at houses-laboratories for the development of the collective farm experimental business - S. D. Kovalenko (History of science and technology, 2015)
The article says about Michurin’s circles at collective farm houses-laboratories that have been working in the horticulture industry. Activities of circles has become an example for a number of researchers who have united around the houses- laboratories as the basis of progress of the collective farm experimental business in the 30-ies. Twentieth century.